50 Years of the Austrian Cartographic Commission - Miljenko Lapaine (Kartografija i Geoinformacije, 2011)
The Austrian Cartographic Commission (Österreichische Kartographische Kommission – ÖKK) of the Austrian Geographic Society (Österreichische Geographische Gesellschaft – ÖGG), as the national representative body for scientific and practical cartography, has celebrated its 50th anniversary.